Surface Modification of Biopolymers - Thakur, Vijay Kumar 1981- (Wiley, 2015)
This book addresses surface modification techniques, which are critical for tailoring and broadening the applications of naturally occurring biopolymers. Biopolymers represent a sustainable solution to the need for new materials in the auto, waste removal, biomedical device, building material, defense, and paper industries.Features: First comprehensive summary of biopolymer modification methods to enhance compatibility, flexibility, enhanced physicochemical properties, thermal stability, impact response, and rigidity, among others Address of a green, eco-friendly materials that is increasing in use, underscoring the roles of material scientists in the future of new "green" bioolymer material use Coverage applications in automotive development, hazardous waste removal, biomedical engineering, pulp and paper industries, development of new building materials, and defense-related technologies Facilitation of technology transfer
Description based on publisher supplied metadata and other sources
Keywords: TECHNOLOGY & ENGINEERING / Material Science; Oberflächenbehandlung; Biopolymere